Copper alloys and electronic parts

The copper alloy with a specific composition of Ni, Co, Si, and Cr addresses the challenge of maintaining high conductivity and strength in miniaturized copper alloy parts for electronic components, achieving enhanced tensile strength and conductivity.

JP7648724B1Active Publication Date: 2025-03-18JX NIPPON MINING & METALS CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023207165
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-12-07
Publication Date
2025-03-18
Estimated Expiration
2043-12-07

AI Technical Summary

Technical Problem

Copper alloy parts in electronic components, such as lead frames in semiconductor packages, face challenges in maintaining high conductivity and strength as they miniaturize, leading to potential deformation and inefficiencies in manufacturing.

Method used

A copper alloy composition containing 2.3 to 4.6% by mass of Ni, 0.10 to 0.50% by mass of Co, 0.60 to 1.3% by mass of Si, 0.010 to 0.10% by mass of Cr, with the remainder being Cu and inevitable impurities, which forms Ni-Co-Si precipitates to enhance strength and conductivity.

Benefits of technology

The copper alloy achieves high tensile strength of 870 MPa or more and conductivity of 30% IACS or more, effectively suppressing deformation during the manufacturing of electronic components and improving manufacturing efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648724000001_ABST
    Figure 0007648724000001_ABST
Patent Text Reader

Abstract

An object of the present disclosure is to provide a copper alloy having high electrical conductivity and high strength, and an electronic component including the same. The copper alloy disclosed herein contains 2.3-4.6 mass% Ni, 0.10-0.50 mass% Co, 0.60-1.3 mass% Si, 0.010-0.10 mass% Cr, and the balance being Cu and unavoidable impurities.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a copper alloy and an electronic component. [Background technology]

[0002] Corson alloy is an alloy in which intermetallic compounds such as Ni-Si, Co-Si, and Ni-Co-Si are precipitated in a Cu matrix, and it has both high strength and high electrical conductivity. Because of these properties, Corson alloy can be used as a copper alloy part in an electronic component, for example, as a lead frame that supports and fixes a semiconductor element in a semiconductor package and forms an internal wiring (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2018-035437 A Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, with the increasing sophistication of electronic components, the copper alloy parts (or specific parts of the copper alloy parts) manufactured from the Corson copper alloy to be included in the electronic components have become highly fine, and there is a demand for copper alloys to have high electrical conductivity while still having improved properties to accommodate this fineness. For example, in semiconductor packages as electronic components, the structure of the semiconductor package has become finer and the package itself has become larger due to the increasing sophistication of the semiconductor package in recent years. For this reason, the lead frames manufactured from copper alloys for constructing semiconductor packages, particularly the leads in the lead frames, have been made finer. The leads are the parts that become the internal wiring (pins) for connecting to external wiring within the semiconductor package, and the lead length has increased and the pitch between the leads has become narrower due to the finer lead sizes. However, such finer sizes can make it difficult for the leads to have sufficient strength, and in the manufacturing process of the lead frame or semiconductor package (for example, a process of manufacturing a desired lead frame by half-etching a copper alloy plate, or a process of arranging a semiconductor element on the lead frame and then performing wire bonding to connect the lead and the semiconductor element), the leads can be deformed and their shape can be difficult to maintain with high precision. As a result, semiconductor packages cannot be manufactured efficiently in some cases, and further improvement in the strength of copper alloys is required.

[0005] An object of the present disclosure is to provide a copper alloy having high electrical conductivity and high strength, and an electronic component including the same. [Means for solving the problem]

[0006] In one embodiment, the copper alloy of the present disclosure is a copper alloy containing 2.3 to 4.6 mass % Ni, 0.10 to 0.50 mass % Co, 0.60 to 1.3 mass % Si, 0.010 to 0.10 mass % Cr, and the balance consisting of Cu and unavoidable impurities.

[0007] In one embodiment, the electronic component of the present disclosure is an electronic component containing the copper alloy of the present disclosure. Effect of the Invention

[0008] The present disclosure can provide a copper alloy having high electrical conductivity and high strength, and an electronic component including the same. [Brief description of the drawings]

[0009] [Figure 1] 1 is a graph in which the properties of the copper alloys of Example 1 and Comparative Examples 1 and 2 are plotted against the Co content (mass%), and a linear approximation curve is drawn. The first axis represents tensile strength, and the second axis represents electrical conductivity. The square plots represent tensile strength, and the circle plots represent electrical conductivity. [Diagram 2] 2 is a graph in which the properties of the copper alloys of Example 1 and Comparative Examples 1 and 2 are plotted against the mass ratio RB of Co to Ni, and a linear approximation curve is drawn. The first axis indicates tensile strength, and the second axis indicates electrical conductivity. The square plot indicates tensile strength, and the circle plot indicates electrical conductivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment of the present disclosure (hereinafter also referred to as "the present embodiment") will be described in detail, but the present invention is not limited to the following embodiment. In the present disclosure, "A to B" means "greater than or equal to A and less than or equal to B," where A and B represent numerical values.

[0011] [Copper alloy] The copper alloy of this embodiment contains 2.3-4.6 mass% Ni, 0.10-0.50 mass% Co, 0.60-1.3 mass% Si, 0.010-0.10 mass% Cr, and the balance is Cu and unavoidable impurities. That is, the copper alloy of this embodiment is a Cu-Ni-Co-Si alloy. Ni, Co, and Si form precipitated particles of Ni-Co-Si intermetallic compounds by appropriate heat treatment, which can achieve high electrical conductivity and high strength.

[0012] In the composition of the copper alloy of this embodiment, the Ni concentration is 2.3 to 4.6 mass%, the Co concentration is 0.10 to 0.50 mass%, and the Cr concentration is 0.010 to 0.10 mass%, which makes it possible to further improve the strength of the copper alloy while maintaining the high electrical conductivity of the copper alloy. If the Ni concentration is less than 2.3 mass%, the desired strength is not obtained. If the Co concentration is less than 0.10 mass%, the desired strength and electrical conductivity are not obtained. If the Cr concentration is less than 0.010 mass%, the desired strength is not obtained. If the Ni concentration exceeds 4.6 mass%, sufficient strength is obtained, but the electrical conductivity is reduced. If the Co concentration exceeds 0.50 mass%, sufficient electrical conductivity is obtained, but high strength is difficult to obtain. If the Cr concentration exceeds 0.10 mass%, Cr forms a compound with other contained components, making it difficult to form the desired Ni-Co-Si-based precipitates. As a result, the desired strength is not obtained. The Ni concentration is preferably 2.8 to 4.4 mass%, more preferably 3.0 to 4.0 mass%, and even more preferably 3.3 to 3.7 mass%. The Co concentration is preferably less than 0.50 mass%, more preferably 0.10 to 0.40 mass%, and even more preferably 0.20 to 0.30 mass%. The Cr concentration is preferably 0.020 to 0.070 mass%, and more preferably 0.040 to 0.060 mass%.

[0013] In the composition of the copper alloy of this embodiment, the concentration of Si is 0.6 to 1.3 mass%. This allows the strength of the copper alloy to be further improved while maintaining the high electrical conductivity of the copper alloy. If the concentration of Si is less than 0.60 mass%, the desired strength cannot be obtained. On the other hand, if the concentration of Si is more than 1.3 mass%, sufficient strength can be obtained, but the electrical conductivity will decrease. The concentration of Si is preferably 0.7 to 1.2 mass %, and more preferably 0.8 to 1.0 mass %.

[0014] As described above, Ni-Co-Si-based precipitates formed by Ni, Co, and Si are considered to be intermetallic compounds mainly composed of (Ni+Co)Si. However, Ni, Co, and Si in a copper alloy do not necessarily become precipitates by aging treatment during the manufacturing process of the copper alloy sheet, and may exist to some extent in a solid solution state in the Cu matrix. Although Ni, Co, and Si in a solid solution state can slightly improve the strength of the copper alloy sheet, the effect is smaller than that in the precipitated state, and they may also be a factor in reducing the electrical conductivity. Therefore, it is preferable that the content ratio of Ni, Co, and Si is close to the composition ratio of (Ni+Co)Si. Therefore, the ratio R of the total mass of Ni and Co to Si is A is preferably 3.5 to 5.0, and more preferably 3.5 to 4.5.

[0015] As described above, Ni-Co-Si precipitates contribute to improving the strength and electrical conductivity of copper alloys, and Ni tends to mainly contribute to improving the strength of copper alloys, while Co tends to mainly contribute to improving the electrical conductivity of copper alloys. Therefore, from the viewpoint of improving the strength of copper alloys while maintaining high electrical conductivity, the mass ratio R of Co to Ni is set to 1.0 to 1.5. B The mass ratio R of Co to Ni can be 0.010 to 0.155. B By making the mass ratio of Co to Ni, R is 0.010 or more, the high electrical conductivity of the copper alloy can be maintained. B By making the ratio of Cr to Mn be 0.155 or less, the strength of the copper alloy can be effectively improved. ratio R B is preferably 0.025 to 0.155, and more preferably 0.056 to 0.086.

[0016] In the composition of the copper alloy of this embodiment, in addition to the above elements, one or more elements selected from the group consisting of Mg, Fe, P, Cr, Ag, Zn, Sn, Pb, Zr, Al, As, Se, Te, Sb, Bi, Au, Ti, Nb, V, Ta, W, Mo and Mn (hereinafter also referred to as "additive elements") may be further contained in a total amount of 0.010 to 1.0 mass %, which can improve the strength, heat resistance, stress relaxation resistance, etc. of the copper alloy. When the total amount of the additive elements is 0.010 mass% or more, the desired effects described above tend to be easily obtained, while when the total amount is 1.0 mass% or less, the desired characteristics can be obtained while preventing a decrease in electrical conductivity. The total amount of the additive elements is preferably 0.020 to 0.080 mass %, and more preferably 0.050 to 0.080 mass %.

[0017] In this embodiment, the balance, which is the components other than those mentioned above, is composed of Cu and inevitable impurities. Here, inevitable impurities refer to impurity elements that are unavoidably mixed into the material during the manufacturing process. The concentration of each element of the inevitable impurities can be, for example, 0.015 mass% or less, and is preferably 0% (undetectable). The composition of the copper alloy can also be measured by wet analysis. For Ni, the copper separation dimethylglyoxime gravimetric method (JIS-H1056 (2003)) can be used, and for Si, the silicon dioxide gravimetric method (JIS-H1061 (2006)) can be used. For other added elements and impurity elements, ICP optical emission spectroscopy can be used, and the analysis of other added elements is performed using the internal standard method, with Y (yttrium) being used as the internal standard. An element other than Y can be selected as the internal standard. For ICP optical emission spectroscopy, measurements are performed using an ICP optical emission spectroscopy analyzer (ICP-OES) SPS3100 manufactured by Hitachi High-Tech Science Corporation or an equivalent device. For ICP optical emission spectroscopy, a sample of the copper alloy is dissolved in a mixed acid containing hydrochloric acid and nitric acid (containing hydrochloric acid, nitric acid, and water in a volume ratio of 2:1:2) and then diluted. The composition of the copper alloy may be measured using X-ray fluorescence analysis. As the X-ray fluorescence analysis device, Rigaku's Simultix14 or an equivalent device can be used. The analysis surface may be cut or mechanically polished so that the maximum surface roughness Rz (JIS-B0601 (2013)) is 6.3 μm or less. When taking a sample for X-ray fluorescence analysis from the molten metal during melting and casting, the molten metal is cast into a shape of about 30 to 40 mmΦ and a thickness of about 50 to 80 mm, and then cut into a thickness of about 10 to 20 mm, and the cut surface is used as the analysis surface. X-ray fluorescence analysis is performed based on JIS K 0119:2008, and the measurement is performed using a wavelength dispersion method.

[0018] The copper alloy of the present embodiment can be made into a copper alloy plate by, for example, a manufacturing method including a rolling step as described below, though it is not particularly limited. The copper alloy plate is not particularly limited as long as it is an object having the above composition and a three-dimensional shape with a predetermined thickness. The "plate" of this copper alloy plate also includes a sheet, a strip, and a foil. In addition, this copper alloy plate includes not only a copper alloy plate before processing for use in, for example, electronic parts, but also a copper alloy plate during or after processing. The thickness of the copper alloy plate is, for example, 0.030 to 1.2 mm. The thickness is preferably 0.050 to 0.60 mm, more preferably 0.080 to 0.30 mm.

[0019] The copper alloy of this embodiment has high electrical conductivity and strength due to the above-mentioned composition. Specifically, the copper alloy of this embodiment may have a tensile strength of 870 MPa or more in a direction parallel to the rolling direction in a copper alloy sheet manufactured through a rolling process. Since the copper alloy has such high tensile strength, it is possible to suppress deformation that may occur during the manufacturing process of electronic components, specifically, during a series of processes up to the manufacturing of electronic components, including the process of manufacturing copper alloy parts (e.g., lead frames) by processing a copper alloy sheet, for miniaturized copper alloy parts for electronic components manufactured from the copper alloy or parts in the copper alloy parts. The tensile strength in the direction parallel to the rolling direction is preferably 930 MPa or more, more preferably 940 MPa or more, and even more preferably 950 MPa or more. stomach. The upper limit of the tensile strength in the direction parallel to the rolling direction is not particularly limited, but the tensile strength may be, for example, 1200 MPa or less, 1100 MPa or less, or 1000 MPa or less.

[0020] The tensile strength in the direction parallel to the rolling direction can be measured using a tensile tester in accordance with JIS-Z2241 (2011). Specifically, a JIS13B test piece is prepared from each sample using a press machine so that the tensile direction is parallel to the rolling direction. The conditions for the tensile test are a test piece width of 12.5 mm, a measurement temperature of room temperature (15 to 35°C), a tensile speed of 5 mm / min, and a gauge length (gauge length) of 50 mm. The test is performed using two test pieces, and the average value of the two data can be used as the tensile strength in the direction parallel to the rolling direction in this disclosure. The above tensile speed corresponds to the crosshead displacement speed described in the JIS standard. Moreover, the tensile strength in the direction parallel to the rolling direction can be adjusted to a desired range by using the copper alloy composition of the above-mentioned copper alloy of this embodiment.

[0021] The copper alloy of the present embodiment may have a conductivity of 30% IACS or more. With a conductivity of 30% IACS or more, the copper alloy can be effectively used as a copper alloy part for electronic components. Electrical conductivity is understood to mean the electrical conductivity in the direction parallel to the rolling direction. Moreover, the electrical conductivity can be adjusted to a desired range by using the copper alloy composition according to the present embodiment described above. Electrical conductivity (EC: %IACS) can be measured by the four-terminal method in accordance with JIS-H0505 (1975). A double bridge is used for the measurement, and resistance can be measured based on the average cross-sectional area method. Electrical conductivity can be measured in a direction parallel to the rolling direction at room temperature (25°C). For convenience of the test sample, the gauge length (distance between electrical resistance measurements) can be set to 50 mm.

[0022] The method for producing the copper alloy sheet will be described below. In this embodiment, the copper alloy sheet can be manufactured by a method including a rolling process, although it is not particularly limited. Specifically, the copper alloy sheet can be manufactured, for example, by homogenizing an ingot, hot rolling, intermediate cold rolling, solution treatment, aging treatment, finish cold rolling, and stress relief annealing in this order. Cold rolling before the solution treatment is not essential and may be performed as necessary. In addition, cold rolling may be performed after the solution treatment and before the aging treatment as necessary, or the solution treatment and the aging treatment may each be performed two or more times. After performing each of the above steps, grinding, polishing, shot blasting, pickling, etc. for removing oxide scale on the surface can be appropriately performed.

[0023] An example of a method for producing a copper alloy sheet that can be produced by a method including a rolling step using the copper alloy of this embodiment will be described in more detail. The method for producing a copper alloy sheet may include a step of melting and casting a raw material of a copper alloy having the above-mentioned desired composition. In this step, the raw material of the copper alloy is melted in the same manner as a general copper alloy melting method, and then an ingot is produced by continuous casting or semi-continuous casting. For example, an air melting furnace is first used to melt raw materials such as electrolytic copper, Ni, Co, Si, and Cr to obtain a molten metal of a desired composition. Then, the molten metal is poured into a mold of any size and cast into an ingot.

[0024] In the present embodiment, the method for producing a copper alloy sheet may include a step of hot rolling an ingot that has been subjected to homogenization annealing. The hot rolling of the ingot is not particularly limited, but may be performed in several passes at 500 to 950°C, for example. The total reduction ratio of the hot rolling is preferably 90% or more.

[0025] The solution treatment is a heat treatment for dissolving silicides such as Ni-Si compounds, Co-Si compounds, and Ni-Co-Si compounds in the Cu matrix and recrystallizing the Cu matrix at the same time. The solution heat treatment temperature is not particularly limited, but can be, for example, 650 to 1000°C. The heat treatment time can be 1 second to 10 minutes. Specifically, by setting the solution treatment temperature and time to the lower limit of the above range or more, even if a large amount of silicides such as Ni-Co-Si compounds are contained in the copper alloy, they can be easily dissolved sufficiently in the Cu matrix and can be recrystallized. By setting the solution treatment temperature and time to the upper limit of the above range or less, it is possible to easily suppress the coarsening of recrystallized grains. The heat treatment temperature is preferably 700 to 950° C., and the heat treatment time is preferably 5 seconds to 5 minutes.

[0026] In the present embodiment, the method for producing a copper alloy sheet may include a step of performing an aging treatment on the intermediate body after the above-mentioned solution treatment. The heat treatment temperature in the aging treatment is not particularly limited, but may be, for example, 375 to 625° C. The heat treatment time may be 0.5 to 50 hours. By setting the aging temperature and time to the lower limit of the above range or higher, the amount of precipitates of Ni-Si compounds, Co-Si compounds, and Ni-Co-Si compounds tends to be sufficient to obtain sufficient strength. By setting the aging temperature and time to the upper limit of the above range or lower, coarsening of precipitates and re-solid solution can be prevented, and strength and electrical conductivity can be easily improved. In order to sufficiently increase the strength and electrical conductivity of the copper alloy, it is important to increase the tensile strength and electrical conductivity of the intermediate body after the aging treatment in a direction parallel to the rolling direction. For example, in order to make the tensile strength of the copper alloy 870 MPa or more, the tensile strength of the intermediate body after the aging treatment may be 750 MPa or more. In order to make the tensile strength of the copper alloy 930 MPa or more, the tensile strength of the intermediate body after the aging treatment may be 830 MPa or more. In order to make the tensile strength of the copper alloy 950 MPa or more, the tensile strength of the intermediate body after the aging treatment may be 850 MPa or more. For example, the electrical conductivity of the intermediate body after the aging treatment in a direction parallel to the rolling direction may be 40% IACS or more. The aging treatment is preferably carried out in an inert atmosphere such as Ar, N2, or H2 in order to suppress the formation of an oxide film.

[0027] In this embodiment, the method for producing a copper alloy sheet may include a step of performing finish cold rolling of the intermediate body. The finish cold rolling is not particularly limited, but may be performed, for example, in several passes. It is preferable to perform one or more passes of rolling. The total processing degree of the finish cold rolling is preferably 40% or more. The finish cold rolling can impart processing strain to the material to improve its strength. The upper limit of the degree of reduction in the finish cold rolling is preferably 90% or less. By keeping the degree of reduction at 90% or less, it is possible to prevent the electrical conductivity from decreasing due to processing distortion caused by strong processing. The degree of reduction (%) is expressed as follows: where TB is the thickness of the workpiece before rolling, and TA is the thickness of the workpiece after rolling: degree of reduction (%) = [(TB-TA) / TB] x 100.

[0028] In this embodiment, the method for producing a copper alloy sheet may include a step of performing stress relief annealing on the intermediate body after the above-mentioned finish cold rolling. The stress relief annealing may be performed under general conditions, for example, at 250°C to 550°C and for a holding time of 5 seconds to 5 hours. The stress relief annealing may be performed in air or in an inert atmosphere such as nitrogen or argon gas. In addition, the copper alloy sheet after stress relief annealing may be cooled by air cooling.

[0029] In this embodiment, the copper alloy sheet can be manufactured by a manufacturing method including the above steps. In this manufacturing method, pickling, polishing, degreasing, facing, and trimming may be performed as necessary after each rolling step and each heat treatment step. In addition, this manufacturing method may include rolling steps and heat treatment steps other than those described above.

[0030] [Electronic components] The electronic component of this embodiment is an electronic component containing the copper alloy of this embodiment described above. More specifically, the electronic component of this embodiment has a copper alloy component manufactured from the copper alloy of this embodiment via a copper alloy plate inside. An example of the electronic component is a semiconductor package. The fine copper alloy component that can be manufactured from the copper alloy of this embodiment has a characteristic of suppressing deformation during the manufacturing process of the electronic component, so that it is suitable to use the copper alloy of this embodiment for manufacturing a semiconductor package having many fine structures. In addition, when the electronic component is a semiconductor package, the semiconductor package can be manufactured, for example, but not limited to, by manufacturing a lead frame using a copper alloy plate manufactured from the copper alloy of this embodiment, supporting and fixing a semiconductor element on the lead frame, wire-bonding the semiconductor element and the leads to form internal wiring, and sealing the semiconductor element with a predetermined resin member. As described above, the electronic component of this embodiment may contain the copper alloy of this embodiment.

[0031] Although the embodiments of the present disclosure have been described above, the copper alloy and electronic component of the present disclosure are not limited to the above examples and can be modified as appropriate.

[0032] Aspects of the present disclosure A first embodiment of the present disclosure is a copper alloy containing 2.3 to 4.6 mass % Ni, 0.10 to 0.50 mass % Co, 0.60 to 1.3 mass % Si, 0.010 to 0.10 mass % Cr, and the balance being Cu and unavoidable impurities.

[0033] A second aspect of the present disclosure is the copper alloy according to the first aspect, containing less than 0.50 wt. % Co.

[0034] A third aspect of the present disclosure is the copper alloy according to the first or second aspect, which contains 0.10 to 0.40 mass % Co.

[0035] A fourth aspect of the present disclosure is the copper alloy according to any one of the first to third aspects, which contains 0.20 to 0.30 mass % Co.

[0036] A fifth aspect of the present disclosure is the copper alloy according to any one of the first to fourth aspects, which contains 0.020 to 0.070 mass % of Cr.

[0037] A sixth aspect of the present disclosure is the copper alloy according to any one of the first to fifth aspects, which contains 3.0 to 4.0 mass % of Ni.

[0038] The seventh aspect of the present disclosure is a ratio R of the total mass of Ni and Co to Si. A is 3.5 to 5.0.

[0039] The eighth aspect of the present disclosure is a method for manufacturing a semiconductor device comprising the steps of: A The copper alloy according to the seventh embodiment, wherein the average molecular weight of the copper alloy is 3.5 to 4.5.

[0040] The ninth aspect of the present disclosure is a method for determining a mass ratio R of Co to Ni. B is 0.010 to 0.155.

[0041] A tenth aspect of the present disclosure is a method for manufacturing a semiconductor device comprising the steps of: B In the copper alloy according to a ninth embodiment, the average molecular weight of the copper alloy is 0.025 to 0.155.

[0042] An eleventh aspect of the present disclosure is a method for manufacturing a semiconductor device comprising the steps of: B In the copper alloy according to a ninth embodiment, the viscosity is 0.056 to 0.086.

[0043] A twelfth aspect of the present disclosure is the copper alloy according to any one of the first to eleventh aspects, further containing 0.010 to 1.0 mass % in total of one or more elements selected from the group consisting of Mg, Fe, P, Cr, Ag, Zn, Sn, Pb, Zr, Al, As, Se, Te, Sb, Bi, Au, Ti, Nb, V, Ta, W, Mo, and Mn.

[0044] A thirteenth aspect of the present disclosure is the copper alloy according to any one of the first to twelfth aspects, which has an electrical conductivity of 30% IACS or more.

[0045] A fourteenth aspect of the present disclosure is the copper alloy according to any one of the first to thirteenth aspects, which has a tensile strength of 870 MPa or more in a direction parallel to the rolling direction.

[0046] A fifteenth aspect of the present disclosure is the copper alloy according to any one of the first to fourteenth aspects, which has a tensile strength of 930 MPa or more in a direction parallel to the rolling direction.

[0047] A sixteenth aspect of the present disclosure is an electronic component comprising the copper alloy according to any one of the first to fifteenth aspects. EXAMPLES

[0048] The present disclosure will be described in more detail below with reference to examples, but the present disclosure is not limited to the following examples in any way. In Example 1, a copper alloy sheet was produced from a desired copper alloy as follows. Using electrolytic copper as the raw material, copper alloys having the compositions shown in Table 1 were melted and cast in an atmospheric melting furnace. These ingots were hot rolled at 950°C to a plate thickness of 10.0 mm. After hot rolling, the plates were faced and then intermediate cold rolled to a plate thickness of 0.167 mm. Then, solution treatment and aging treatment were performed under the conditions shown in Table 1. Next, the sheets were finish cold-rolled to a thickness of 0.1 mm with a working ratio shown in Table 1 to obtain copper alloy sheets. In Example 2, the copper alloy sheet subjected to the finish cold rolling in Example 1 was further subjected to stress relief annealing in air under the conditions shown in Table 2. The copper alloy sheet after stress relief annealing was cooled by air cooling to obtain the copper alloy sheet of Example 2.

[0049] In Comparative Examples 1 and 2, copper alloy sheets were manufactured in the same manner as in Example 1, except that the composition of the copper alloy and the solution treatment conditions were changed to those shown in Table 1. Specifically, in Comparative Example 1, the composition of the copper alloy was changed to that shown in Table 1, and the temperature condition of the solution treatment was changed to 900 ° C. or 925 ° C. as shown in Table 1. Two samples were manufactured as copper alloy sheets by the same manufacturing method as in Example 1. The evaluation of each copper alloy in Comparative Example 1 was performed by plotting the numerical values ​​of the evaluation results of the two samples (tensile strength and electrical conductivity of the intermediate body after aging treatment and the copper alloy sheet after finish cold rolling as shown in Table 1) on the vertical axis and the solution treatment temperature on the horizontal axis, calculating a straight line connecting the plots, and then substituting the value of the solution treatment temperature of 915 ° C. into the formula representing the straight line, thereby obtaining each estimated evaluation result of the copper alloy and its intermediate body when the solution treatment was performed at 915 ° C. In Comparative Example 2, similarly to Comparative Example 1, the composition of the copper alloy was changed to that shown in Table 1, and the solution treatment temperature was changed to 910°C, 935°C, and 950°C as shown in Table 1. Except for this, three samples were manufactured as copper alloy sheets by the same manufacturing method as in Example 1. The evaluation of each copper alloy in Comparative Example 2 was carried out by plotting the numerical values ​​of the evaluation results of the three samples on the vertical axis and the solution treatment temperature on the horizontal axis, calculating an approximate line connecting the plots (using the approximate line function of Microsoft Excel (registered trademark)), and then substituting the value of the solution treatment temperature of 915°C into the formula representing the approximate line, thereby obtaining each estimated evaluation result of the copper alloy and its intermediate when the solution treatment was carried out at 915°C.

[0050] The obtained copper alloy sheets of Examples 1 and 2 and the copper alloy sheets of Comparative Examples 1 and 2 were subjected to the following measurements. The results are shown in Tables 1 and 2. 〔composition〕 The composition of the obtained copper alloy was confirmed by X-ray fluorescence analysis. The X-ray fluorescence analyzer used was a Simultix14 manufactured by Rigaku Corporation. The analyzed surface was cut or mechanically polished so that the maximum surface roughness Rz (JIS-B0601 (2013)) was 6.3 μm or less. X-ray fluorescence analysis was performed based on JIS K 0119:2008, and measurements were taken using a wavelength dispersion method.

[0051] [Tensile strength (TS)] The tensile strength (TS) of the obtained copper alloy sheet was measured in a direction parallel to the rolling direction using a tensile tester in accordance with JIS-Z2241 (2011). Specifically, JIS 13B test pieces were prepared from each sample using a press machine so that the tensile direction was parallel to the rolling direction. The conditions for the tensile test were: test piece width 12.5 mm, measurement temperature room temperature (15-35°C), tensile speed (crosshead displacement speed) 5 mm / min, and gauge length 50 mm. The test was performed using two test pieces, and the average values ​​of the two data are shown in Tables 1 and 2.

[0052] 〔conductivity〕 Electrical conductivity (EC: %IACS) was measured by the four-terminal method in accordance with JIS-H0505 (1975). A double bridge was used for the measurement, and resistance was measured based on the average cross-sectional area method. Electrical conductivity was measured in the direction parallel to the rolling direction at room temperature (25°C). The gauge length (distance between electrical resistance measurements) was 50 mm.

[0053] [Table 1]

[0054] [Table 2]

[0055] As shown in Tables 1 and 2, it was found that by manufacturing with a desired composition, the tensile strength was improved while having high electrical conductivity. Therefore, the fine copper alloy parts for electronic components manufactured from the copper alloys of Examples 1 and 2 can suppress deformation during the manufacturing process of the electronic components. The properties (tensile strength and electrical conductivity) of the copper alloys of Example 1, Comparative Example 1, and Comparative Example 2 were plotted against the Co content (mass%), and the linear approximation curve was drawn, as shown in FIG. 1. It is considered that the electrical conductivity improves as the Co content increases, because Co-Si-based precipitates or Ni-Co-Si-based precipitates are generated. Therefore, a linear approximation curve was created from the experimental values ​​obtained in the examples, and the electrical conductivity at each Co content was predicted. From this result, it can be seen that if the Co content is 0.10 mass% or more, electrical conductivity of 39.7% IACS or more can be realized. If the Co content is 0.20 mass% or more, electrical conductivity of 39.8% IACS or more can be realized. If the Co content is 0.25 mass% or more, electrical conductivity of 39.7% IACS or more can be realized. If the Co content is 0.25 mass% or more, electrical conductivity of 40.1% IACS or more can be realized. The properties (tensile strength and electrical conductivity) of the copper alloys of Example 1, Comparative Example 1, and Comparative Example 2 were compared by the mass ratio R of Co to Ni. B The results are shown in Figure 3, where the linear approximation curve is plotted against R. B It is considered that as R increases, Co-Si precipitates or Ni-Co-Si precipitates are generated, so that electrical conductivity is easily obtained but strength is difficult to obtain. Therefore, a linear approximation curve was created from the experimental values ​​obtained in the examples, and each R B The strength and electrical conductivity at the ratio R B It can be seen that if the ratio R is 0.010 or more, a conductivity of 39.7% IACS or more can be achieved. B It can be seen that if the ratio R is 0.025 or more, a conductivity of 39.7% IACS or more can be achieved. B It can be seen that if the ratio R is 0.056 or more, a conductivity of 39.8% IACS or more can be achieved. B It can be seen that if the ratio R is 0.155 or less, a tensile strength of 938 MPa or more can be achieved. BIt can be seen that if is 0.086 or less, a tensile strength of 949 MPa or more can be achieved. [Industrial Applicability]

[0056] According to the present disclosure, it is possible to provide a copper alloy having high electrical conductivity and high strength, and an electronic component including the same.

Claims

1. A copper alloy containing 2.3 to 4.6 mass% Ni, 0.20 to 0.50 mass% Co, 0.60 to 1.3 mass% Si, 0.010 to 0.10 mass% Cr, with the balance being Cu and unavoidable impurities, and having a tensile strength of 870 MPa or more in a direction parallel to the rolling direction.

2. 2. The copper alloy of claim 1 containing less than 0.50% by weight of Co.

3. The copper alloy according to claim 2, containing 0.20 to 0.40 mass% Co.

4. The copper alloy according to claim 3, containing 0.20 to 0.30 mass% Co.

5. The copper alloy according to claim 1, containing 0.020 to 0.070 mass% Cr.

6. The copper alloy according to claim 1, containing 3.0 to 4.0 mass% Ni.

7. Ratio of the total mass of Ni and Co to Si, R A The copper alloy according to claim 1, wherein the Mn content is 3.5 to 5.

0.

8. The ratio R A The copper alloy according to claim 7, wherein the Mn content is 3.5 to 4.

5.

9. Mass ratio of Co to Ni R B The copper alloy of claim 1, wherein the Mn content is 0.010 to 0.

155.

10. The ratio R B The copper alloy according to claim 9, wherein the Mn content is 0.025 to 0.

155.

11. The ratio R B The copper alloy according to claim 9, wherein the Mn content is 0.056 to 0.

086.

12. The copper alloy according to claim 1, further containing 0.010 to 1.0 mass% in total of one or more elements selected from the group consisting of Mg, Fe, P, Ag, Sn, Pb, Zr, As, Se, Te, Sb, Bi, Au, Ti, Nb, V, Ta, W, Mo and Mn.

13. 2. The copper alloy of claim 1, having an electrical conductivity of 30% IACS or greater.

14. 2. The copper alloy according to claim 1, having a tensile strength in a direction parallel to the rolling direction of 930 MPa or more.

15. The alloy contains 2.3 to 4.6 mass% Ni, 0.10 to 0.50 mass% Co, 0.60 to 1.3 mass% Si, 0.010 to 0.10 mass% Cr, and the balance is Cu and unavoidable impurities. The mass ratio R of Co to Ni is B is a copper alloy having a melting point of 0.056 to 0.

086.

16. The copper alloy according to claim 15, further containing 0.010 to 1.0 mass% in total of one or more elements selected from the group consisting of Mg, Fe, P, Ag, Zn, Sn, Pb, Zr, As, Se, Te, Sb, Bi, Au, Ti, Nb, V, Ta, W, Mo and Mn.

17. 17. An electronic component comprising the copper alloy according to any one of claims 1 to 16.

Citation Information

Patent Citations

  • Cu-ni-si-based copper alloy for electronic material

    JP2007107062A

  • Cu-Ni-Si-Co-Cr-BASED ALLOY FOR ELECTRONIC MATERIAL

    JP2009242921A

  • Cu-Ni-Co-Si-BASED COPPER ALLOY SHEET MATERIAL, MANUFACTURING METHOD THEREOF AND ELECTRIFICATION COMPONENT

    JP2015183263A

  • Copper alloy for electronic and electric device, copper alloy thin sheet for electronic and electric device, component and terminal for electronic and electric device

    JP2016050326A

  • ELECTRONIC COMPONENT Cu-Ni-Co-Si ALLOY

    JP2016176105A